Under‐referral of Plain community members for genetic services despite being qualified for genetic evaluation. Issue 4 (4th April 2021) - Ehrenberg, Sarah; Walsh Vockley, Catherine; Nelson, Erica; Baker, Jennifer; Arcieri, Michael; Lindenberger, Jessica; Ghaloul‐Gonzalez, Lina
Abstract: Plain community people (Amish and Mennonites) have increased risk of having recessive genetic disorders. This study was designed to assess the rate of referral of Plain people to genetic services at UPMC Children's Hospital of Pittsburgh. Medical records of Plain patients from a 1‐year time period were reviewed. Data collected included demographic information, clinical presentation, referral for genetic services, and diagnosis. Of the 303 patients, 102 (33.7%) had a clinical presentation suggestive of a genetic disorder, yet only 32 of those 102 patients (31.4%) had been evaluated by the division of Medical Genetics. These data indicate that less than half of Plain patients with a clinical presentation suggestive of a genetic disorder had been referred to the division of Medical Genetics for a formal evaluation. Now that under‐referral of Plain patients has been confirmed, providers can be educated in order to increase referrals for genetic services and facilitate positive healthcare outcomes for the Plain Community.